Factors influencing housing affordability for generation Y / Zafirah Yussof and Nurulanis Ahmad @ Mohamed - Yussof, Zafirah; Ahmad @ Mohamed, Nurulanis (2018)
In recent years, housing prices have increased tremendously thus affecting people's purchasing power. In Malaysia, Generation Y prefers to live in the city because of convenience and lifestyle. However, living in cities with many facilities provided results in higher housing prices. As a response to these, the government has introduced housing programs to increase affordability by providing affordable homes for every state in Malaysia. Nevertheless, the supply of affordable houses still cannot cater to the needs of far too many Malaysians. There are still many who faced problems to own and buy affordable housing because of their financial constraints or their low levels of income. Meanwhile, housing affordability in various states and countries across the globe has considerable attention from year to year. For instant, the State of Perak, Malaysia (District of Perak Tengah) has been recorded as the worst issue in housing affordability. Each country will experience different factors on affordability matters due to the socio economic profile of the country. Therefore, the aim of this research is to identify and rank the main factors influencing housing affordability for Generation Y, focusing among Generation Y in Bandar Seri Iskandar, State of Perak. In this study, the quantitative method will be employed by distributing questionnaire survey to 100 public respondents. The distribution of questionnaire among Generation Y used simple random sampling. Through SPSS analysis, the study has analyzed the main factors contributing to housing affordability. This study has found out that demographic is the main factor influencing housing affordability for Generation Y in Seri Iskandar.